Pengukuran Prestasi Belajar Matematika Siswa dengan Menggunakan Tes Model Testlet ditinjau dari Status Sekolah dan Gender - Nila Hayati; Rasyid Hardi Wirasasmita; Mimi Alpian; Sri Supiyati (Universitas Hamzanwadi, 2021)
This study aims to determine the differences in students' mathematics learning achievement as measured using the testlet model test in terms of school status and gender in class VII SMP/MTs students. This study uses a quantitative approach in the form of ex post facto research. This study took samples from 2 public schools and two private schools with a total sample of 109 students. The sampling technique used is purposive sampling. Data collection techniques using test techniques and instruments using a testlet model test based on local wisdom. The instrument's validity uses content validity with the Aiken formula, while the reliability, level of difficulty of distinguishing power, and the effectiveness of distractors are analyzed by the ITEMAN 3.0 application. The data analysis technique used was two-way Analysis of Variance (ANOVA). Based on the results of the data analysis conducted, it can be seen that there is no difference in students' mathematics learning achievement as measured by using the testlet model test when viewed from school status or in terms of gender. The analysis results also show that school status and gender are not related to improving students' mathematics learning achievement when measured using the testlet model test.